1996
DOI: 10.1302/0301-620x.78b1.0780005
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Loosening in Cemented Custom-Made Prosthetic Replacements for Bone Tumours of the Lower Limb

Abstract: W e have made a retrospective study of 1001 custom-made prostheses used as replacements after surgery for bone tumours. There were 493 distal femoral, 263 proximal femoral and 245 proximal tibial prostheses. Aseptic loosening was shown to be the principal mode of failure of the implants, and 71 patients had revision for aseptic loosening of a cemented intramedullary stem.The probability of a patient surviving aseptic loosening for 120 months was 93.8% for a proximal femoral replacement, 67.4% for a distal femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
366
5
8

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(404 citation statements)
references
References 9 publications
25
366
5
8
Order By: Relevance
“…At a median of 90 months (range, 24-181 months), the median MSTS score of the 21 patients who retained their implant was 27 (range, [24][25][26][27][28][29][30]). An active 90°arc of motion of the affected knee was maintained in 17 (81%) patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a median of 90 months (range, 24-181 months), the median MSTS score of the 21 patients who retained their implant was 27 (range, [24][25][26][27][28][29][30]). An active 90°arc of motion of the affected knee was maintained in 17 (81%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Three patients required secondary operations for cortical insufficiency proximal to the anchor plug in bone not spanned by the CPS implant and unrelated to the prosthesis. Median MSTS score was 27 (range, [24][25][26][27][28][29][30]. Conclusions Revision distal femoral replacement arthroplasty after a failed megaprosthesis is often difficult as a result of a lack of adequate bone.…”
mentioning
confidence: 99%
“…In a large study by Jeys et al [13], including 228 distal femoral EPRs, aseptic loosening accounted for 13.6% of all failures with a median time to revision due to mechanical failure of 9.3 years. Moreover, Mittermayer et al [20] and Unwin et al [27] found, at 10 years postoperatively, 24% and 32.6%, respectively, of patients who had distal femoral EPR underwent revision for aseptic loosening. In our current study, the overall rate of aseptic failure was 7.7% at 6.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The relative length of prosthetic replacement has been associated with distal femoral prosthetic failure, particularly when the femoral resection exceeds 40% of the overall length of the femur. Reduction of the femoral deficiency to less than 40% of the overall bone length may mitigate this effect [9,11]. There is a tradeoff, however.…”
Section: Discussionmentioning
confidence: 99%